Penerapan Regularisme dalam Pembiasaan Ibadah Santri: Perspektif Psikologi Agama di Pondok SMP Misbahul Khair - Mutiara, Yolanda; Azizah, Nur; Zakya, M Yusron (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This study examines the implementation of regularism in the habituation of students’ religious practices at Pondok SMP Misbahul Khair, analyzed from the perspective of the psychology of religion. Regularism, understood as religious behavior performed consistently, systematically, and repeatedly, plays a crucial role in shaping the spiritual character of students within the pesantren environment. The purpose of this research is to explore how structured religious activities—such as congregational prayers, morning and evening dhikr, Qur’an recitation, and other daily religious routines—affect students’ psychological development, particularly in terms of discipline, emotional stability, spiritual awareness, and the formation of long-term religious habits. Using a qualitative approach with direct observation, in-depth interviews, and documentation of students’ daily activities. The findings indicate that the implementation of regularism not only encourages disciplined worship practices but also significantly contributes to the psychological growth and religious character formation of students. Therefore, regularism can serve as an effective model for faith-based educational institutions in fostering sustainable spiritual development among learners.